Immediate Effects of Maternal Deprivation on the (Re)Activity of the HPA-Axis Differ in CD1 and C57Bl/6J Mouse Pups - Daskalakis, Nikolaos P.; Enthoven, Leo; Schoonheere, Edwige; de Kloet, Edo Ronald; Oitzl, Melly S. (Frontiers in Endocrinology, 2014)
The postnatal development of the mouse is characterised by a period of hypo-responsiveness of the hypothalamic-pituitary-adrenal (HPA) axis to mild stressors. Maternal deprivation (MD) during this period can disrupt the quiescence of the HPA-axis. The present study examined the influence of strain (outbred CD1 versus inbred C57BL/6J mice) on some central and peripheral components of the HPA-axis in neonatal mice (5 day-old) in the presence of their mother or after 24 h MD (on postnatal day 4) under basal or mild stressful conditions. In the presence of the dam, adrenal corticosterone (CORT) secretion was low in both mouse strains. Compared to CD1 mice, C57BL/6J had lower CORT levels associated with higher ACTH levels and ACTH/CORT ratio (i.e., lower adrenal sensitivity to ACTH), and higher glucocorticoid receptor (GR) mRNA expression in the paraventricular nucleus. Although MD disinhibited the HPA-axis in both strains as reflected by increased basal CORT and ACTH, we found a strain-dependent pattern. MD increased CORT more in C57BL/6J, compared to CD1 mice, together with a lower ACTH/CORT ratio (i.e., higher adrenal sensitivity to ACTH), while GR mRNA was no longer different in the two strains. However, this increased adrenal sensitivity in maternally deprived C57BL/6J mice was not reflected in their CORT response to a subsequent novelty stressor, possibly due to a MD-induced ceiling effect in their steroidogenic capacity. In conclusion, the immediate outcome of MD depends on the genetic background of the mother-infant dyad, suggesting that maybe also the outcome in later-life cannot be generalized. genetic background of the mother-infant dyad, predicting that the outcome in later-life cannot be generalized.